2013
DOI: 10.4149/neo_2013_071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of ascites in epithelial ovarian cancer

Abstract: The prognostic significance of ascites in the dissemination of metastases in epithelial ovarian cancer (EOC) is unclear. Our study aimed to investigate the association between clinicopathological factors and the development of ascites, as well as its prognostic significance. Three hundred and thirty three patients with primary EOC were suitable for inclusion. We analyzed the correlation between clinicopathological factors, including the extent of metastases, and ascitic volume. The prognostic significance of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 16 publications
3
43
0
1
Order By: Relevance
“…Age, stage, response to surgery (optimal vs. sub-optimal), and initial platinum-free interval are the strongest predictors of overall clinical outcome [2]. Some clinical factors associated with surgical outcome include pre-operative CA 125, spread of disease on pre-operative imaging, hematologic parameters, extent of disease identified at the time of surgery, and presence or absence of ascites [24]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, stage, response to surgery (optimal vs. sub-optimal), and initial platinum-free interval are the strongest predictors of overall clinical outcome [2]. Some clinical factors associated with surgical outcome include pre-operative CA 125, spread of disease on pre-operative imaging, hematologic parameters, extent of disease identified at the time of surgery, and presence or absence of ascites [24]. …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have identified the presence of ascites and volume of ascites as negative prognostic factors in patients with ovarian cancer [4, 810]. It is unclear from these studies whether ascites is simply a manifestation versus a driver of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, 61% of patients present at an advanced stage, and despite therapeutic advances, only 27% survive for 5 years after diagnosis [1]. One of the reasons for late diagnosis is that ovarian cancer is asymptomatic until the occurrence of abdominal bloating or swelling, symptoms commonly associated with ascites and metastases beyond the ovary [2]. Peritoneal ascites are a distinguishable feature of patients with advanced ovarian cancer, and is a result of the inflammatory response triggered by the malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The presence and progression of ascites are associated with grim survival statistics, a decreased quality of life, and may have predictive value for malignant ovarian tumors [3,5,11,[14][15][16][17]26,31,[99][100][101][102]. The predictive value of ascites remains a source of debate, as is the case with most clinical and biological markers for this challenging disease [98,[103][104][105]. Ascites in ovarian cancer patients is treated by managing the underlying disease, typically via surgical resection and adjuvant platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, an estimated 85% of ovarian cancer patients who achieve remission following first-line therapy will develop recurrent disease, which is associated with a median survival of 12 to 24 months [2,12,14,105]. Intractable ascites often develop in these patients, a major co-morbidity that is managed by draining the fluid to temporarily alleviate the associated pain and discomfort [3,5,14,103,104]. Treatment approaches to reduce ascites and improve chemotherapy efficacy include the use of anti-vascular endothelial growth factor agents as well as targeting the renin-angiotensin system [3,5,14].…”
Section: Discussionmentioning
confidence: 99%